Genome-Wide Identification of the Bcl-2 Associated Athanogene (BAG) Gene Family in Solanum lycopersicum and the Functional Role of SlBAG9 in Response to Osmotic Stress - Hailong Jiang; Yurong Ji; Jiarong Sheng; Yan Wang; Xiaoya Liu; Peixiang Xiao; Haidong Ding (MDPI AG, 2022)
The Bcl-2-associated athanogene (BAG) proteins are a family of multi-functional group of co-chaperones regulators, modulating diverse processes from plant growth and development to stress response. Here, 10 members of SlBAG gene family were identified based on the available tomato (Solanum lycopersicum) genomic information and named as SlBAG1-10 according to their chromosomal location. All SlBAG proteins harbor a characteristic BAG domain, categorized into two groups, and SlBAG4, SlBAG7, and SlBAG9 of group I contain a plant-specific isoleucine glutamine (IQ) calmodulin-binding motif located in the N terminus. The quantitative real-time PCR expression analysis revealed that these SlBAG genes had organ-specific expression patterns and most SlBAG genes were differentially expressed in multiple abiotic stresses including drought, salt, high temperature, cold, and cadmium stress as well as abscisic acid and H2O2. In addition, heterologous overexpression of SlBAG9 increased the sensitivity of Arabidopsis to drought, salt, and ABA during seed germination and seedling growth. The decreased tolerance may be due to the downregulation of stress-related genes expression and severe oxidative stress. The expression levels of some stress and ABA-related genes, such as ABI3, RD29A, DREB2A, and P5CS1, were significantly inhibited by SlBAG9 overexpression under osmotic stress. Meanwhile, the overexpression of SlBAG9 inhibited the expression of FSD1 and CAT1 under stress conditions and the decreased levels of superoxide dismutase and catalase enzyme activities were detected accompanying the trends in the expression of both genes, which resulted in H2O2 accumulation and lipid peroxidation. Taken together, these findings lay a foundation for the future study of the biological function of SlBAG genes in tomato.